Operações sustentáveis e desempenho : revisão sistemática e metanálise - D'Agostini, Marina (My University, 2015)
Sustainability is rapidly emerging as one of the most important topics for business strategy and have been explored in a lot of research lines. However, the relation between sustainable practices and performance shows divergent results and still there are studiesthat can’t prove a direct relation between the variables. Thus, the literature about this issue shows an inconclusive feature, providing opportunity for this search that aimedto determine whether there is a relationship between sustainable operations practices and performance categories and whether there are moderatingacting in this relationship. Sustainable operations practices considered include ecodesign, green supply chain, cleaner production and reverse logistics, while the performance was divided into environmental, economic, operational and organizational.Connect these sustainable operations practices with performance categories there was obtained 16 hypothesis. Due to the goal of this research to seek a theoretical consensus that contributes to the evolution of knowledge about a specific issue, the methodology applied was a systematic review followed by a meta-analysis. The systematic review initially found 3.825 studies of which 37 had the parameters required to perform the meta-analysis and were effectively used.As results, thehypothesis of the relationship between reverse logistics and organizational performance can’t be tested due to insufficient data and, among the others hypotheses, only one was not accepted: the relationship between green supply chain practices and economic performance. About the moderating , they don’t acting in two relationships: ecodesign and operational performance and cleaner production and organizational performance, showing that in these relations there aren’t factors interfering in their results.
A sustentabilidade emerge rapidamente como um dos principais tópicos para estratégia de negócios e tem sido explorada em diversas frentes de pesquisa. No entanto, a relação entre as práticas sustentáveis e o desempenho apresenta-sedivergente e há ainda estudosque não conseguem comprovar uma relação direta entre estas variáveis. Sendo assim, a literatura sobre este tema apresenta uma característica inconclusiva, o que oportunizou esta pesquisa,cujo objetivo foiverificar se existe relação entre as práticas de operações sustentáveis e as categorias de desempenho e, ainda, se existem fatores moderadores atuando nestas relações. As práticas de operações sustentáveis consideradas incluem ecodesign, cadeia de suprimentos verdes (GSC), produção mais limpa (P+L) e logística reversa, enquanto o desempenho foi dividido em desempenho ambiental, desempenho econômico, desempenho operacional e desempenho organizacional.Relacionando estas práticas sustentáveis com as categorias de desempenho obteve-se 16 hipóteses.Devido ao caráter desta pesquisa em buscar um consenso teórico que contribua para a evolução do conhecimento sobre um tema específico, a metodologia aplicada foi a de revisão sistemática seguida de metanálise. A revisão sistemática encontrou inicialmente 3.825 estudos, dos quais 37 tinham os parâmetros requeridos para realização da metanálise e foram efetivamente utilizados. Como resultados, a hipóteseda relação entre logística reversa e desempenho organizacional não pôde ser testada por insuficiência de dados e, das demais hipóteses, apenas uma não foi aceita: a relação entre as práticas de cadeia de suprimentos verdes e o desempenho econômico. Os moderadores não atuam em duas relações: ecodesign e desempenho operacional, e P+L e desempenho organizacional, mostrando que nestas relações não há fatores interferindo em seus resultados.
Keywords: Administração; Desenvolvimento sustentável; Ecodesign; Management; Sustainable development; Sustainable design